Energy stored during deformation of crystallizing TPU foams. (28th March 2018) - Lachhab, A.; Robin, E.; Le Cam, J.‐B.; Mortier, F.; Tirel, Y.; Canevet, F.
Abstract: The hysteresis loop observed in the mechanical response of elastomers is classically assumed to be due to viscosity. In this study, a complete energy balance is carried out during cyclic deformation of compact and foamed crystallizing thermoplastic polyurethanes. Results show that viscosity is not the only phenomenon involved in the hysteresis loop formation: A significant part of the mechanical energy brought is not dissipated into heat and is stored by the material when the material changes its microstructure, typically when it is crystallizing. Some of this energy is released during unloading, when melting occurs, but with a different rate, which contributes to the hysteresis loop. The part of the mechanical energy stored by the material has been quantified through the γ s e ratio (Loukil et al. (2018) European Polymer Journal, 98, 448–455) to investigate the effects of the loading rate and the void volume fraction on the energetic response of thermoplastic polyurethane.